Causes of attrition among frontline health workers in rural areas of Bauchi and Cross River States of Nigeria. (13th April 2021) - Okech, M; Okoroafor, S C; Ojo, O; Mohammed, B
ABSTRACT: Background: The situation of frontline health workers in the rural areas of Bauchi and Cross River States has been classified as critical regarding the shortages due to attrition. This affects health service delivery and outcomes. Methods: We targeted 402 participants, and 389 frontline health workers (nurses, midwives, nurse/midwives, community health officers and community health extension workers) responded. They were drawn from 42 public primary healthcare centers: 23 from Cross River and 19 from Bauchi States. Five focused-group discussions were conducted with 42 facilities in-charges to identify what they perceived as the main causes of attrition in the rural areas. Results: Our findings indicate that the reasons that had potential to cause attrition of the frontline health workers were either voluntary or involuntary. Out of the 81 nurses in the study, 66 (81 percent) would voluntarily exit the workforce while 15 (19 percent) would leave involuntarily. From a total number of 81 nurses, midwives and nurse/midwives from the two states, 75% would exit due to resignations in search of better prospects in the urban areas. Ninety-nine percent of the community health worker's attrition had very low intentions of exit, and it would mainly be due to retirements and deaths. Conclusion: Implementation of tailor-made strategies that reflect their needs is imperative in the two states to reduce attrition among frontline health workers and improve health service outcomes.